Building Capacities for Scaling-Up Climate Smart Village in Nepal: A training manual - Pudasaini, Roshan; Adhikari, Laxmi Devi; Bhusal, Aastha; Paudel, Bikash; Khatri-Chhetri, Arun (Local Initiatives for Biodiversity, Research and Development, Nepal, 2019)
Globally there has been enormous effort made by thousands of organizations to promote Climate Smart Agriculture (CSA) technologies for the sake of building resilience in agriculture and farmers’ livelihood. However, the progress so far is not satisfactory. Based on the past learnings CCAFS has conceptualized the idea of Climate Smart Village (CSV) which has CSA as the major component, along with other political and socio-economic dimensions. Looking at the successful piloting of CSV, the Government of Nepal has endorsed this approach in its program. However, a mechanism to share the idea of CSV to the development bodies is lacking. Similarly, the extension workers and other staffs of local governments do not have enough procedural understanding. Therefore, to scale-up CSV approach in Nepal, capacity building of government staffs and local leaders, especially at local and provincial level, is an absolute necessity. A guide book could be the means to facilitate the process of such capacity building. Hence this manual is developed as a guide book for organizing capacity building trainings to the government and non-government development professionals. It will also serve as a resource book to help development workers from local and provincial governments, local leaders, policy makers, researchers, and academicians to understand more about the idea and approach of CSV. Ultimately, this publication is expected to contribute to the mission of scaling-up the CSV approach for the enhanced resilience of farming communities in Nepal and around the world.